The US Agricultural Act of 2014: Overview and analysis - Zulauf, Carl; Orden, David (International Food Policy Research Institute, 2014)
This paper summarizes the evolutionary trends in US farm policy that have culminated in the 2014 farm bill, describes the new farm bill programs in depth, and highlights the key policy issues that arise and will play out over its planned five-year duration. This new US farm bill eliminates fixed direct payments made to farmers since 1996. In place of those payments, the 2014 farm bill strengthens protections against downside price and revenue risks. Crop insurance is enhanced as a pillar of the US farm safety net. In addition, new programs are enacted to address two types of loss: shallow losses that coincide with the deductible on individual farm insurance and losses resulting from multiple years of low prices or declining revenue that are not covered by insurance. Because of the lack of consensus on the design of assistance programs for such risks, farmers are given choices among several program options. The strengthened safety net will result in less certain annual support payments to farmers, with spending that could prove lower or higher than had the 2014 farm bill not been enacted.